Implementasi Kartu Tanda Penduduk Elektronik (KTP-El) di Mal Pelayanan Publik Kabupaten Pamekasan - Aurely Kartika Sari; Indah Prabawati; Tjitjik Rahayu; Firre An Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The implementation of the Electronic Identity Card (KTP-el) policy is a government effort to realize orderly population administration through electronic-based public services. The problems that occur in implementing the KTP-el policy are the server system that is difficult for employees to access to input population data in making electronic KTPs, as well as aspects of infrastructure resources, namely the limited KTP-el forms and recording devices that are not running optimally in supporting the KTP-el service process. This study aims to describe the Implementation of Electronic Identity Cards in the Pamekasan Regency Public Service Mall. The research method used is through a qualitative approach with a descriptive research type. The data obtained are primary data through interviews and observations and secondary data through documentation results. The results show that the Implementation of Electronic Identity Cards is based on four policy implementation variables (Communication, Resources, Disposition, Bureaucratic Structure). The implementation of KTP-el has been running quite well, but is still not optimal, namely in the resource variable, there are still limitations in the number of employees, as well as facilities and infrastructure on KTP-el recording devices that are not running optimally and limited electronic KTP forms. Researchers suggest that it is necessary to improve the server system and add e-KTP forms and also related to increasing budget resources to optimize recording tools and maintenance of existing facilities.